PENGARUH AUDIT TENURE, KOMITE AUDIT, DAN FEE AUDIT TERHADAP KUALITAS AUDIT (STUDI EMPIRIS PERUSAHAAN SEKTOR ENERGY YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2022-2024) - Wardah Rasikhah Sucipto; Sri Handayani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Audit quality reflects the extent to which auditors are able to provide assurance that financial statements have been presented fairly in accordance with applicable accounting standards. This study aims to analyze the effect of Audit Tenure, Audit Committee, and Audit Fee on Audit Quality in Energy sector companies listed on the Indonesia Stock Exchange for the period 2022–2024. Audit Tenure is proxied by the number of consecutive years a company has been audited by the same public accounting firm, Audit Committee is proxied by calculating the number of members of the company's audit committee, Audit Fee is proxied by the natural logarithm (Ln) of the total audit fees paid by the company, and Audit Quality is proxied using a dummy variable based on the audit opinion given by the auditor, WTP Opinion (score 1) and Non-WTP Opinion (score 0). This research is quantitative research with a causality design. The data used is secondary data accessed through the official website of the Indonesia Stock Exchange (IDX) and the official websites of each company. The population of this study is all companies in the Energy sector listed on the Indonesia Stock Exchange in 2022-2024, with sampling techniques using purposive sampling, resulting in 68 companies as samples, producing 204 observations. The data analysis method used is logistic regression`n analysis using statistical tool. The results of the study indicate that Audit Tenure, Audit Committee, and Audit Fee simultaneously have a significant effect on Audit Quality. Furthermore, the results of the study partially indicate that Audit Fee has a positive effect on Audit Quality, while Audit Tenure and Audit Committee do not affect Audit Quality. In practical terms, this research can be used as a consideration for company management to improve audit quality by providing adequate audit fees so that auditors can carry out audit procedures optimally, thereby ensuring that the financial statements issued have a high level of fairness and reliability. Theoretically, this study supports agency theory, which shows that the existence of external auditors as independent parties plays a role in ensuring that the information conveyed by management to investors is trustworthy and not misleading in decision making.